Performance Analysis of Doubly Excited Brushless Generator with Outer Rotor for Wind Power Application - Yingchao Zhang; Huijuan Liu; Haijiao Zhang; Xiang Zhao (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
In this paper, a novel doubly excited brushless generator (DEBG) with outer radial laminated magnetic barrier rotor (RLMB-rotor) for wind power application was designed and analyzed. The DEBG has 10 rotor pole numbers with outer rotor. Its performance was investigated using the 2D transient finite element method. The magnetic fields, torque capability, end winding voltage characteristics, radial magnetic force and energy efficiency were analyzed. All studies in this paper show that the simplicity, reliability, high efficiency and low vibration and noise of the DEBG with outer rotor were attractive for variable speed constant frequency (VSCF) wind power generation system.